SOCIAL LEARNERS REQUIRE PROCESS INFORMATION TO OUTPERFORM INDIVIDUAL LEARNERS. (5th October 2012) - Derex, Maxime; Godelle, Bernard; Raymond, Michel
Abstract : Humans exhibit a rich and complex material culture with no equivalent in animals. Also, social learning, a crucial requirement for culture, is particularly developed in humans and provides a means to accumulate knowledge over time and to develop advanced technologies. However, the type of social learning required for the evolution of this complex material culture is still debated. Here, using a complex and opaque virtual task, the efficiency of individual learning and two types of social learning (product‐copying and process‐copying) were compared. We found that (1) individuals from process‐copying groups outperformed individuals from product‐copying groups or individual learners, whereas access to product information was not a sufficient condition for providing an advantage to social learners compared to individual learners; (2) social learning did not seem to affect the exploration of the fitness landscape; (3) social learning led to strong within‐group convergence and also to between‐group convergence, and (4) individuals used widely variable social learning strategies. The implications of these results for cumulative culture evolution are discussed.